ANALISA EMISI GAS BUANG KENDARAAN BERMOTOR RODA EMPAT PADA RUAS JALAN IR.M.PUTUHENA WAILELA –AMBON - Novi. N. Tetelepta; Edison Effendi (Journal Mechanical Engineering, 2023)
Indonesia is a huge market share for potential sales of motorized vehicles of various types and brands, this can be seen from the large growth rate of motorized vehicles which exceeds 15% per year (BPS, 2011) or 7.9 million vehicles per year. The high growth of motorized vehicles is not only supported by Indonesia's large population (240 million), but also by the characteristics of Indonesians who are happy to change vehicles to show their existence and prestige in society.In addition, government regulations that do not violate the growth of motorized vehicles have also contributed to the high growth rate of motorized vehicles in Indonesia. The high growth rate of motorized vehicles, on the one hand, can boost the rate of economic growth, but on the other hand, it can cause very serious environmental impacts. Air pollution caused by motorized vehicles greatly affects human health.Vehicles produced under 2007 contribute a large amount of emissions, this can be seen from the results of the emission test analysis on the Ir.M Putuhena road section, 103 vehicles or 0.29% give an average Carbondioxide (CO) emission level of 3.125%. while for Hydrocarbon(HC) the number of vehicles that did not pass was 4% of the 103 test vehicles with an average of 141.41 ppm, Keywords: exhaust emissions, quality standards, hydrocarbons, carbon dioxide